Quercitrin restrains the growth and invasion of lung adenocarcinoma cells by regulating gap junction protein beta 2. Issue 3 (1st March 2022) - Li, Deng Yun; Yue, Li Xiao; Wang, Shi Guang; Wang, Tian Xiao
ABSTRACT: Lung adenocarcinoma (LUAD) is the most prevalent subtype of non-small cell lung cancer (NSCLC) with high lethality, and quercitrin exhibits anticancer characteristics. Here, we attempted to uncover the anticancer activity of quercitrin in LUAD. In this work, quercitrin prohibited the cell viability and clone-formation of LUAD cells in vitro . Meanwhile, quercitrin treatment reduced the aggressive phenotypes in LUAD cells. Further, Gap Junction Protein Beta 2 (GJB2) expression was aberrantly higher in LUAD when compared within control tissue. The higher expression of GJB2 is associated with an inferior overall survival for patients with LUAD. Finally, the reintroduction of GJB2 offset the inhibiting influence of quercitrin in LUAD cells. Altogether, these findings disclosed that quercitrin suppressed the growth and metastatic-related traits of LUAD cells partly via regulating GJB2 expression. Graphical abstract: uf0001